2010
DOI: 10.1016/j.polymer.2009.05.003
|View full text |Cite
|
Sign up to set email alerts
|

In-situ fabrication of polyacrylate–silver nanocomposite through photoinduced tandem reactions involving eosin dye

Abstract: . In-situ fabrication of polyacrylate-silver nanocomposite through photoinduced tandem reactions involving eosin dye. Polymer, Elsevier, 2010, 51 (6) ABSTRACTA silver-acrylate nanocomposite was prepared using a novel one-pot strategy involving eosin dye as visible sensitizer and an amine derivative as radicals source. The mechanism highlighted by steady state photolysis and time resolved absorption spectroscopy lies on the initial formation of a strong ion pair complex between eosin and Ag + . Upon visible ir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0
3

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 68 publications
(39 citation statements)
references
References 68 publications
0
36
0
3
Order By: Relevance
“…It was reported in several cases that the preliminary addition of any metal nanoparticle seeds is required to form NPs but the direct photoreduction of silver cations could also occur by the presence of an excited chromophores or by an intermediate reactant which is generated in-situ during excitation [23]. For example, Malval et al [24], reported the photoinduced synthesis of monodisperse ligandcoated silver nanoparticles, where Ag + ion was reduced by R-aminoalkyl radicals.…”
Section: Evidence Of the Reductant Role Of The Hydrogelsmentioning
confidence: 99%
See 1 more Smart Citation
“…It was reported in several cases that the preliminary addition of any metal nanoparticle seeds is required to form NPs but the direct photoreduction of silver cations could also occur by the presence of an excited chromophores or by an intermediate reactant which is generated in-situ during excitation [23]. For example, Malval et al [24], reported the photoinduced synthesis of monodisperse ligandcoated silver nanoparticles, where Ag + ion was reduced by R-aminoalkyl radicals.…”
Section: Evidence Of the Reductant Role Of The Hydrogelsmentioning
confidence: 99%
“…The coordination between Ag-NPs and nitrogen atoms of the amides, hydroxyl groups or carbonyl oxygen in PNIPAM seem to increase VPTT as a consequence of the immobilization of polymer on the NPs surface or vice versa [23]. Taking into account the change of VPTT (∆T) between the nanocomposite and the respective hydrogel, and its ratio to the amount of NPs (∆T/mg Ag-NPs), it is possible to conclude that the interactions of AgNPs with PNIPAM are strong.…”
Section: Volume Phase Transition Temperaturementioning
confidence: 99%
“…When associated with DMPA, [Ag](PPh 3 ) could be also used to ameliorate the kinetics of photopolymerization of acrylate monomers and promote the formation of in situ Ag NPs for antibacterial applications. Photochemical reduction of silver salts (generally AgSbF 6 ) to synthesize Ag NPs in polymer coatings under inert conditions or according to a cationic photopolymerization process has already been described in literature . Well‐defined Ag NPs with different sizes have been synthesized under light irradiation; however, silver salts have never shown any accelerating effects as regards the polymerization kinetics under air.…”
Section: Resultsmentioning
confidence: 99%
“…Other methodologies also allow the formation of Ag or Au NPs in solution (see refs . or in films (even in situ during the polymerization of the monomer formulations). The incorporation of Ti NPs for example is of great challenge (see refs .…”
Section: Introductionmentioning
confidence: 99%